Men's perception of paternal parenthood and the promotion of child development - Gustavo Selenko de Aquino; Sarah de Almeida Rocha Moura; Ailton de Lima Junior; Samara Macedo Cordeiro; Jéssica Batistela Vicente; Verônica de Azevedo Mazza (Associação Brasileira de Enfermagem, 2024)
ABSTRACT Objectives: to comprehend men's perception of paternal parenthood while caring for infants to promote child development. Methods: this qualitative study adopts an exploratory approach and was conducted with undergraduate and graduate students, faculty, and staff who are fathers of infants up to 6 months old from a higher education institution, excluding fathers from mononuclear families. Data collection occurred through semi-structured interviews and was analyzed using thematic categorical analysis. Results: fifteen men participated in the study. From the analysis, two empirical categories emerged: "Perception of being a father: challenges and novelties" and "Promotion of child development: actions carried out by fathers". Fathers revealed feeling unprepared, the need for emotional support, and recognized activities aimed at their children's development. Final Considerations: the relevance of the paternal figure for child development is highlighted, as well as the need for public policies to encourage paternal parenthood.